Chemical Castration as a Punishment for Child Rapists from a Human Rights Perspective: An Analysis of Judgment No. 859/Pid.Sus/2023/PN.Bjm - Gratsya Defretes; Akhmad Faqih Mursid (Journal of Law Justice (JLJ), 2026)
This study aims to analyze the application of chemical castration as a punishment for child rapists from a human rights perspective, focusing on Court Decision No. 859/Pid.Sus/2023/PN.Bjm as the subject of the study, as well as its compliance with the principle of humanity. The method used in this study is a descriptive-analytical normative legal method employing both a statutory approach and a case-based approach, involving a qualitative analysis of primary, secondary, and tertiary legal sources. The novelty of this study lies in its specific examination of the judge’s reasoning in imposing chemical castration on the perpetrator in Judgment No. 859/Pid.Sus/2023/PN.Bjm, as well as the relationship between regulations and judicial practice, which has not been extensively studied. The results of the study indicate that the imposition of chemical castration as an additional penalty for the perpetrator of child rape in the aforementioned judgment is normatively intended to protect the victim, in this case the child, and to prevent the recurrence of similar criminal acts. However, this has become controversial from a human rights perspective because it pertains to the perpetrator’s right to bodily integrity, as stipulated in Law No. 39 of 1999 and Articles 28G through 28J of the 1945 Constitution of the Republic of Indonesia. Furthermore, in this ruling, the imposition of chemical castration on the perpetrator was also based on the judge’s subjective considerations without regard to the cumulative requirements for restricting rights under Law No. 17 of 2016, Article 81, paragraph (7), resulting in inconsistencies that potentially violate the principle of proportionality between statutory regulations and judicial practice. The conclusion of this study is that chemical castration sentences not based on clear legal provisions and human rights standards have the potential to create inconsistencies in the application of the law and violate the principle of proportionality regarding the offender’s right to bodily integrity.